Empowerment and agricultural production: Evidence from rural households in Niger - Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2016)
Niger is a landlocked Sahelian country, two-thirds of which is in the Sahara desert, with only one-eighth of the land considered arable. Nevertheless, more than 90 percent of Niger’s labor force is employed in agriculture, which is predominantly subsistence oriented. Since the great famines of the 1970s and 1980s, the country has pursued agrarian intensification through technological change to address challenges to the food security situation. However, this approach has failed to recognize that the main characteristic of the Sahelian part of West Africa is the intricate complexity of the social, environmental, and economic dimensions that differentially affect male and female rural dwellers. One example is the patrilineal tenure system, which under increased population pressure has led to the exclusion of women and youth from agriculture in some areas. The Women’s Empowerment in Agriculture Index (WEAI) indicates that access to land is one important dimension of empowerment. In order to assess the role of empowerment in agricultural production, we use new household- and individual-level WEAI data from Niger and regression analysis. Our results show that empowerment is important for agricultural production and that households in which adult individuals are more empowered are more productive. This means that other and possibly more effective pathways to agrarian intensification exist and important agricultural productivity gains could be made by empowering men and women in rural households.